Frequency of Molar Pregnancy in Abortion Cases Diagnosed by Histopathology Specimens at Nishtar Medical University Hospital, Multan Pakistan - Shafi, Shazia; Perveen, Shahida; Qureshi, Asim Iqbal; Munir, Ayesha; Qureshi, Hina Zahra; Gul, Pari Iman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of molar pregnancy in abortion cases diagnosed by histopathology specimens. Study Design: A cross-sectional study. Place and Duration of the Study: Department of Obstetrics & Gynecology, Nishtar Medical University Hospital, Multan from March 2020 to November 2020. Material and Methods: A total of 243 pregnant women with singleton pregnancy aged 18 to 40 years with gestational age below 22 weeks presenting with abortion and admitted to labor ward of Nishtar Medical University Hospital, Multan were included. Both suction and sharp curettage specimens were obtained and submitted to the institutional pathology department for histopathological examination. Presence of molar pregnancy was noted. Results: In a total of 243 women, mean age of the women was 29.6±4.5 years while 112(46.1%) women were aged between 26 to 30 years. Mean gestational age was 16.9±3.4 weeks whereas 39(16.0%) women were in their 1st trimester of pregnancy and 204(84.0%) in 2nd trimester of pregnancy. A total of 142(58.4%) women belonged to rural areas of residence. There were 58 (23.9%) women who were illiterate. Molar pregnancy was noted in 5(2.1%) patients, out of which, there were 2 cases of complete mole and 3 cases of partial mole. Conclusion: Frequency of molar pregnancy in this study was 2.1% including 2 cases of complete and 3 cases of partial mole.